Inhibitory effect of Curcumin on phosphorylation NFκB-p65 induced by hydrogen peroxide in Bovine Endothelial Cells - Narges Sharifat; Farideh Jafari-Hafshejani; Parisa Dayati; Parastoo Lorestanpoor; Ali Paydar; Hossein Babaahmadi Rezaei (Fasa University of Medical Sciences, 2017)
Background & Objective: NFκB is a dimeric transcription factor with multiple subunits. Phosphorylation of  p65 (one of NFκB subunits) by oxidative stress leads to the activation of NFκB. Imbalance between oxidative stress and cellular antioxidant capacity is the pathogenesis of many diseases. Consuming antioxidants in daily meal can be considered as a preventive strategy for inflammatory diseases. Among antioxidant components, curcumin is a natural polyphenol which is extracted from Tumeric. Curcumin can protect the human body from oxidative stress by neutralizing the free radicals. Material & Methods: Bovine Endothelial Cells (BECs) were treated with different concentration of H2O2 (10, 20, 80, 200 μM). To investigate the inhibitory effect of curcumin on H2O2 mediated phosphorylation of p65, BECs were incubated with 5 and 10μM concentration of curcumin. Protein concentration was measured by Bradford method and phosphorylation of p65 was assessed by western blotting. Results: Our finding indicated that p65 phosphorylation was increased two fold in presence of H2O2 (200 μM) in comparison with control. The enhancing effect of H2O2 on p65 phosphorylation decreased at 30 min (P: 0.03) and 2 hours (P:0.015) after treatment with 10 μM dose of curcumin. Conclusion: The result of this study indicates that one of anti-inflammatory mechanisms of curcumin is through NFκB pathway by inhibition of p65 subunit phosphorylation.